Comprehensive Midwifery Care For Mrs “K” With A Normal Pregnancy At The Klinik Lumpangan Public Health Center - Sri Eka Juniarli; Iramaya Sari; Risnawati; Aldina Lestari; Nabila; Kurnia (Jurnal Life Birth, 2022)
Pregnancy is a physiological condition, but in pregnancy it is important to be screened in the process of pregnancy, especially in the III trimester of pregnancy. The obstetric care provided is comprehensive care covering the processes of pregnancy, childbirth, newborns, puerperium, neonates, and birth control. Comprehensive obstetric care uses a continuous care approach by monitoring the development of the mother and fetus in monitoring the gestation period until the use of contraceptives or birth control. The methods of care in this LTA are in-person interviews, patient observations, and home visits with SOAP documentation. The subject in this upbringing was Mrs "K" GIP0A0 with a normal pregnancy at the Lumpangan Clinic. The results of comprehensive obstetric care in Mrs "K" during pregnancy trimesters III with mild Anemia, no complications and complications were found, in childbirth with spontaneous childbirth, presentation of the back of the head, without any complications, physiological newborns with no IMD, in puerperium with normal puerperium without any complications, physiological neonates, and family planning by using injectable contraceptives 3 months. The conclusion from the results of obstetric care is obtained by carrying out independent care and early treatment if any difficulties are found. It is expected for midwives to improve quality services and increase actions for maternal health.